Secondary education in Ethiopia : supporting growth and transformation - Joshi, R. D. (Rajendra Dhoj) (World Bank e-Library., 2012)
Becoming a middle-income economy is an explicit development goal of many countries in Sub-Saharan Africa. This book assesses the implications of that goal for secondary education in Ethiopia. It shows that a rapid expansion of secondary education will be needed to support the country?s transition from a low-income economy with substantial subsistence agriculture to a lower-middle-income economy with an increased share of commercial agriculture, as well as growing industrial and service sectors. As Ethiopia moves towards this goal, the demand for a labor force with skills beyond basic literacy.